ANALISIS KESULITAN SISWA SMK KELAS X DALAM MENYELESAIKAN SOAL MATERI LOGARITMA - Seni Marwanti; Wahyu Setiawan; Nelly Fitriani (IKIP Siliwangi, 2022)
This research aims to describe the results of the analysis of the difficulties of class X SMK students in solving logarithm material problems. The research method used in this study is a qualitative descriptive method. The subjects of the study were 14 students of class X Nurses at SMK Kesehatan Bakti As-Syukur. The research instrument consisted of 5 logarithm material test questions. The data collection technique used in this study was in the form of test results by looking at the location of students' errors in solving questions. The data processing technique used is to calculate the percentage of student mastery of the questions with Microsoft Excel 2010 to be able to analyze student difficulties. The results of the study show that only question number 3 has a percentage of mastery of the material which is still below 72% so it can be said that most students still have difficulty in solving problem number 3 which has indicators of manipulating logarithm forms based on logarithm properties. From the results of the analysis, it can be concluded that the difficulty of class X SMK students in solving logarithm problems lies in the indicators of manipulating the logarithm form based on the properties of logarithms, namely; (1) Students have difficulty in simplifying.